REKRUTMEN TENAGA AHLI (TA) ANGGOTA DPR RI DAN DAMPAKNYA TERHADAP KUALITAS KINERJA TENAGA AHLI - Ervina Auliya; Yuwanto Yuwanto (Journal of Politic and Government Studies, 2026)
This study examines the recruitment patterns of Expert Staff (TA) members of the Indonesian House of Representatives (DPR RI) and its impact on the quality of TA performance as stakeholders and supporting staff in supporting DPR members in carrying out their duties. The background of the study stems from findings that TA member recruitment is conducted in a closed manner based on member prerogatives, relationships, personal closeness, party recommendations, and extra organizational ties. This recruitment mechanism has the potential to reinforce negative public assumptions about the DPR RI's performance and reduce the quality of support provided by TA members. This study used a descriptive qualitative method with data collection techniques of interviews, observation, and documentation. The research location was within the DPR RI, with informants selected through purposive sampling. The results indicate that TA recruitment regulations serve only as an administrative framework, such as data and file verification conducted by the Secretariat General, while candidate eligibility decisions are dominated by members' prerogatives. This recruitment pattern opens up space for informal recruitment based on personal networks, political contributions, rewards, and organizational/party affiliations, potentially indicating patronage/spoils system practices. This type of recruitment pattern creates a mismatch between professional needs and the competencies possessed by TA candidates.